LONGITUDINAL MAGNETORESISTANCE OF P-TYPE SILICON UNDER UNIAXIAL ELASTIC DEFORMATION - L.U. Taimuratova; A. Seitmuratov (Academic Journal of Physical and Chemical Sciences, 2019)
An increase in the mobility of holes and electrons at uniaxial stress (compression or tension) was found, that is important in the technology of manufacturing transistors. We present the results of the pyezo resistance phenomenon, which increases the mobility of holes and electrons when uniaxial pressure is applied to the main crystallographic axes. It means the transformation by uniaxial pressure of the isoenergetical surface.